Tribocorrosion of a CoCrMo alloy sliding against articular cartilage and the impact of metal ion release on chondrocytes. (August 2019) - Stojanović, B.; Bauer, C.; Stotter, C.; Klestil, T.; Nehrer, S.; Franek, F.; Rodríguez Ripoll, M.
Graphical abstract: Abstract: Partial knee replacement and hemiarthroplasty are some of the orthopedic procedures resulting in a metal on cartilage interface. As metal implant material, CoCrMo based alloys are commonly used. The aim of the present study is to assess the role of biotribocorrosion on the CoCrMo-cartilage interface with an emphasis on metal release during sliding contact. The biotribocorrosion experiments were performed under controlled electrochemical conditions using a floating cell with a three electrode set up coupled to a microtribometer. Throughout the experiment the coefficient of friction and the open circuit potential were monitored. Analyses of the electrolyte after the experiment show that metal release can occur during sliding contact of CoCrMo alloy against articular cartilage despite the extraordinary low coefficient of friction measured. Metal release is attributed to changes in passive layer caused at the onset of sliding. The released metal was found to be forming compounds with potential cytotoxicity. Since the presence of metal ions in the cartilage matrix can potentially lead to cell apoptosis, the metabolic activity of human osteoarthritic chondrocytes (2D-cultures) was investigated in the presence of phosphate buffered saline containing metal ions using XTT-assay. The experiments indicate that critical concentrations of Co ions lead to a significant decrease in chondrocyte metabolic activity. Therefore, biotribocorrosion is a mechanism that can occur in partial replacements and lead to chondrocyte apoptosis thus playing a role in the observed accelerated degradation of the remaining cartilage tissue after the mentioned orthopedic procedures. Statement of Significance: Partial replacements provide an alternative to total joint replacements. This procedure is less invasive, allows a faster rehabilitation and provides a better function of the joint. However, the remaining native cartilage experiences accelerated degradation when in contact with metallic implant components. This work investigates the role of tribocorrosion at the metal-cartilage interface during sliding. Tribocorrosion is a degradation process that can alter significantly the wear rates experienced by metallic implants and lead to the release of metal ions and particles. The released metal can form compounds with potential cytotoxicity on cartilage tissue. The knowledge gained in this work will serve to understand the mechanisms behind the failure of partial replacements and develop future biomaterials with an enhanced lifetime.